Methodological and Contextual Foundations of Metacognitive Monitoring Training Program in Student Self-Regulated Learning - Balashov, Eduard; Pasichnyk, Ihor; Kalamazh, Ruslana (Journal of Education Culture and Society, 2022)
Aim. This manuscript aims to present the theoretical and contextual characteristics of the developed training program focused on identifying the components of students’ self-regulated learning activities with the use of metacognitive monitoring as well as improving the effectiveness of the students’ learning activities at the individual-personal, motivational-volitional, cognitive and metacognitive levels. To do this, we sought to analyze these phenomena in scientific literature and develop a training program aimed to develop students’ reflexivity, internal learning motivation, and metacognitive skills; to inform students about the features of metacognitive monitoring and metacognitive control of self-regulated learning activities, their awareness of the characteristics of their own processes of understanding, evaluating and reproducing information; to form comprehension and task analysis skills, as well as understanding of the specifics of performed tasks. Methods. A system of general scientific methods was used: analysis and synthesis of the main characteristics of the concepts of self-regulated learning and metacognitive monitoring as a complex multidimensional formation, comprehension of the psychological foundations of self-regulated learning, systematization and generalization of scientific provisions of metacognitive monitoring in student self-regulated learning. This study focused on the design and development of the training program for increasing the efficiency of metacognitive monitoring in student self-regulated learning. Results. The presented manuscript has analyzed the theoretical aspects of the concepts of metacognitive monitoring and self-regulated learning of HEI students. The theoretical essence of the methodological and contextual characteristics of the above mentioned phenomena has been studied. The role and importance of metacognitive monitoring and its components in the learning efficiency and academic self-regulation of HEI students have been described. It has been determined that metacognitive monitoring as a metacognitive characteristic of personality determines not only the organization of mental and behavioral processes, but also relates to the academic success of the subject of learning activity, namely the student. The training program for increasing the efficiency of metacognitive monitoring in student self-regulated learning has been developed and presented. Conclusions. The program was designed to help students consciously approach the independent planning and setting of learning goals, control intellectual and metacognitive activities, and use cognitive and metacognitive strategies in learning, monitoring, controlling and correcting their learning activities. Since these processes provide students with cognitive understanding of their own cognitive processes, the use of this type of training program will help students optimize their learning outcomes through metacognitive monitoring in the process of self-regulated learning activities.